2022
DOI: 10.1038/s10038-021-01001-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of common aneuploidy in twin pregnancies

Abstract: The incidence of chromosomal abnormalities in twin pregnancies is not well-studied. In this retrospective study, we investigated the frequency of chromosomal abnormalities in twin pregnancies and compared the incidence of chromosomal abnormalities in dichorionic diamniotic (DD) and monochorionic diamniotic (MD) twins. We used data from 57 clinical facilities across Japan. Twin pregnancies of more than 12 weeks of gestation managed between January 2016 and December 2018 were included in the study. A total of 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“… 19 Studies have shown that twin pregnancies are more likely to have fetal structural abnormalities than singleton pregnancies and that twin pregnancies have specific complications during pregnancy. 20 In this study, a total of 504 twin pregnancies were included, and the results showed that the sensitivity of NIPT in the detection of both singleton and twin pregnancies groups was 100%. Notably, the specificity in the latter group was slightly lower, and the PPV was also lower than that in the singleton pregnancy group, which may be because twin pregnancy is more prone to placenta mosaic and leads to false positives.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“… 19 Studies have shown that twin pregnancies are more likely to have fetal structural abnormalities than singleton pregnancies and that twin pregnancies have specific complications during pregnancy. 20 In this study, a total of 504 twin pregnancies were included, and the results showed that the sensitivity of NIPT in the detection of both singleton and twin pregnancies groups was 100%. Notably, the specificity in the latter group was slightly lower, and the PPV was also lower than that in the singleton pregnancy group, which may be because twin pregnancy is more prone to placenta mosaic and leads to false positives.…”
Section: Discussionmentioning
confidence: 89%
“…Confounding factors such as confined placental mosaicism, maternal chromosomal anomalies, and maternal background of CNV and CPM may be attributed to the false positives. 20 , 21 Therefore, when interpreting NIPT results, it is vital to take into account these factors. Pregnant subjects should be provided with professional post-test genetic counseling to ensure a thorough understanding of the results.…”
Section: Discussionmentioning
confidence: 99%